Quantum Network Coding Algorithms in Wireless Systems - Debnath, Baishakhi; Garg, Richa; Dadhich, Atul (International Conference on Computing, Communication, and Networking Technologies (Online), 2024)
The speed of verbal exchange has been advanced in cordless networks, which allow everybody to enter records and equipment. However, Wi-Fi channels needing to be more flexible can cause decreased throughput, loss of information, and potential long latencies. Quantum community coding algorithms are a hopeful paradigm to counter these problems as they reduce the impact of network imperfections, hence bringing about superior gadget efficiency. In other words, they help solve the issues of potential and error propagation by encoding data with quantum properties such as entanglement and superposition. This enables more messages on the same channel to be transmitted promptly, with higher throughput and lower latency. They also use the natural correlations present in Wi-Fi environments for more reliable communication, providing enhanced security and privacy. Quantum networking coding algorithms, if realized in wireless communications, may want to substantially revolutionize how we send data and allow a new technology of solid and comfortable networked systems.